Interaction of TWEAK with Fn14 leads to the progression of fibrotic liver disease by directly modulating hepatic stellate cell proliferation2. Issue 1 (29th March 2016) - Wilhelm, Annika; Shepherd, Emma L; Amatucci, Aldo; Munir, Mamoona; Reynolds, Gary; Humphreys, Elizabeth; Resheq, Yazid; Adams, David H; Hübscher, Stefan; Burkly, Linda C; Weston, Christopher J; Afford, Simon C
Abstract: Tumour necrosis factor‐like weak inducer of apoptosis (TWEAK) and its receptor fibroblast growth factor‐inducible 14 (Fn14) have been associated with liver regeneration in vivo . To further investigate the role of this pathway we examined their expression in human fibrotic liver disease and the effect of pathway deficiency in a murine model of liver fibrosis. The expression of Fn14 and TWEAK in normal and diseased human and mouse liver tissue and primary human hepatic stellate cells (HSCs) were investigated by qPCR, western blotting and immunohistochemistry. In addition, the levels of Fn14 in HSCs following pro‐fibrogenic and pro‐inflammatory stimuli were assessed and the effects of exogenous TWEAK on HSCs proliferation and activation were studied in vitro . Carbon tetrachloride (CCl4 ) was used to induce acute and chronic liver injury in TWEAK KO mice. Elevated expression of both Fn14 and TWEAK were detected in acute and chronic human liver injury, and co‐localized with markers of activated HSCs. Fn14 levels were low in quiescent HSCs but were significantly induced in activated HSCs, which could be further enhanced with the profibrogenic cytokine TGFβ in vitro . Stimulation with recombinant TWEAK induced proliferation but not further HSCs activation. Fn14 gene expression was also significantly up‐regulated in CCl4 models of hepatic injury whereas TWEAK KO mice showed reduced levels of liver fibrosis following chronic CCl4 injury. In conclusion, TWEAK/Fn14 interaction leads to the progression of fibrotic liver disease via direct modulation of HSCs proliferation, making it a potential therapeutic target for liver fibrosis. © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.